Solve Using the Square Root Property (x-9)(x-2)=0

Math
(x-9)(x-2)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
x-9=0
x-2=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
x-9=0
Add 9 to both sides of the equation.
x=9
x=9
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
x-2=0
Add 2 to both sides of the equation.
x=2
x=2
The final solution is all the values that make (x-9)(x-2)=0 true.
x=9,2
Solve Using the Square Root Property (x-9)(x-2)=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top